ANALYSIS OF THE INFLUENCE OF CELEBRITY ENDOSER AND SOCIAL MEDIA MARKETING ON BRAND AWARENESS IN E-COMMERCE CUSTOMERS - Zulkarnaen, Wandy; Fitriani, Iis Dewi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
With the Covid-19 pandemic, technological disruption is increasingly rapid and increasing, causing people to carry out activities from home. This makes companies increase new creations and innovations to survive the competition, so companies use celebrity endorsers as promotional media and increase social media marketing to build brand awareness. This research is quantitative research using a non-probability sampling method with a sample size of 100 respondents obtained through distributing Google forms. The measurement scale carried out by researchers used the Bipolar Adjective scale using multiple linear regression techniques which were processed using SPSS 26. The results of this research are that celebrity endorsers and social media marketing have a positive influence with correlation coefficient values of 0.460 and 0.118 on brand awareness. The significance value of celebrity endorsers is 0.000 and the significance value of social media marketing is 0.044, which means less than 0.005, indicating that the influence of celebrity endorsers and social media marketing on brand awareness is acceptable or significant.